Sistem Informasi Perusahaan Pada E - Bussines - Wanda Aprilly Charos; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
This research was written with the aim of knowing how company information systems work in e-business. This research was written using the library research method or library research using several books and journals as the source of this research. Library research is research that does not use research data such as observations and interviews. The data source used is secondary data from journals and books related to the material for writing this paper. The background of this research is how management information systems are used in online businesses. The results of this study can be seen that the information system is a combination of software, hardware, and telecommunication networks to collect useful data, especially within an organization. Few companies today are built entirely on information technology, such as eBay, Amazon, Alibaba and Google. There are 4 types of known information systems namely operations support systems, management information systems, decision support systems andexecutive information systems